2008
DOI: 10.1590/s1020-49892008000800004
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of pneumococcal conjugate vaccination in Brazil, Chile, and Uruguay

Abstract: Objectives. To evaluate the economic impact of vaccination with the pneumococcal 7-valent conjugate vaccine (PCV7) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
(31 reference statements)
2
23
0
10
Order By: Relevance
“…The projected annual burden of disease using cumulative 5-year incidence in LA&C showed 10.5 million AOM cases for the region for a birth cohort of 11.7 million, resulting in a similar cumulative incidence percentage (89%), with 12% estimated to be caused by pneumococcus [47]. Total events of pneumococcal otitis media have been projected to be 108 events per 1000 children in Brazil, Chile and Uruguay (projected for the 2005 birth cohort during the first five years of life) [48]. Compared to this conservative assumption for this region, the reported incidence was 80-fold lower in Arevalo Silva et al [18] (incidence 1.1%), 2.5-fold lower in Nandi-Lozano et al [28] (incidence 36.0%), while intermediate values were observed in Gutierrez Trujillo et al [31] (incidence 4.5%) and Lopez 1998 (incidence 2.7%) [27].…”
Section: Discussionmentioning
confidence: 97%
“…The projected annual burden of disease using cumulative 5-year incidence in LA&C showed 10.5 million AOM cases for the region for a birth cohort of 11.7 million, resulting in a similar cumulative incidence percentage (89%), with 12% estimated to be caused by pneumococcus [47]. Total events of pneumococcal otitis media have been projected to be 108 events per 1000 children in Brazil, Chile and Uruguay (projected for the 2005 birth cohort during the first five years of life) [48]. Compared to this conservative assumption for this region, the reported incidence was 80-fold lower in Arevalo Silva et al [18] (incidence 1.1%), 2.5-fold lower in Nandi-Lozano et al [28] (incidence 36.0%), while intermediate values were observed in Gutierrez Trujillo et al [31] (incidence 4.5%) and Lopez 1998 (incidence 2.7%) [27].…”
Section: Discussionmentioning
confidence: 97%
“…The purpose of this study was to evaluate the cost-effectiveness of including the PCV10 into the routine childhood immunisation in Brazil. Previous studies evaluated the cost-effectiveness of an immunisation programme with PCV7 in Brazil, and their results suggested that this programme would be a very cost-effective intervention 4 5. To our knowledge this is the first study assessing the cost-effectiveness of an immunisation programme with PCV10, the vaccine introduced in the Brazilian NIP.…”
Section: Introductionmentioning
confidence: 89%
“…The most frequent serotype isolated in children with meningitis in the region was serotype 14 in 28.5% of the samples (95% 44 Chile, 29,48 Uruguay 29,48,58 and the LAC region globally. 50 The pooled mean length of stay per pneumococcal meningitis case was 15 days (95% CI: 12.6-17.5).…”
Section: Resultsmentioning
confidence: 99%